SYATIIMAH (SWEAR WORDS) AMONG YOUNG LEARNERS: A CASE STUDY OF SMA NEGERI 1 MAKASSAR - M. Syaiful; Armien Harry Zainuddin (Jurnal Al-Dustur, 2020)
As the student of SMA Negeri 1 Makassar though of swear words, they truly realized that it is prohibited to express, in certain time and condition. In other cases, they as the student oftentimes express it in their daily conversation. The researcher isinterested indiscussingthe utterances which contain swear words on the student of SMA Negeri 1 Makassar as one ofspeech communityin Makassar. This research aims todetermine the category and to find outthe intended meaningof the swear words they express.The researcherusesthe descriptive qualitative method to describe the mentionedscope of the problem abovebecause this research has the primary data in the form of utterances that contains swear words which provides rich description about its meaning and category.The approach of this research uses pragmaticsfor the analysis of the context and SPEAKING factors to assist pragmatics in describing the context and find the intended meaning.As the results, the researcher found that the categories of expressed swearing words in this research are 1. One’s Mother in Law (Sundala; Bitch); 2. Certain Game or Animal (Tolo; Bangsat; Goblok/Geblek; Anjing/Anjay/Anjir; Damn; Asu); 3. Sex/Copulative Term (Fuck); 4. Death (Setan); and 5. Excretion (Tai; Telaso; Shit).The intended meaning of swearing words which expressed by the student of SMA Negeri 1 Makassar is mostly based on its connotative meaning, as the expression of startled and anger. Thus, the intended meaning of the expressions are as the normal response of what is being happened, for casual conversation.